2005
DOI: 10.1007/s11615-005-0249-2
|View full text |Cite
|
Sign up to set email alerts
|

Physische Attraktivität und Wahlerfolg. Eine empirische Analyse am Beispiel der Wahlkreiskandidaten bei der Bundestagswahl 2002

Abstract: Obgleich eine große Zahl von Publikationen zum Attraktivitäts-Stereotyp existiert, sind die Wirkungen der physischen Attraktivität von Politikern weitgehend unerforscht. Dies gilt insbesondere im Hinblick auf den Zusammenhang zwischen physischer Attraktivität und Wahlerfolg. Am Beispiel der Bundestagswahl 2002 wird untersucht, wie sich die Attraktivität der Wahlkreiskandidaten auf ihren Erststimmenanteil auswirkt. Die Attraktivität wird dabei durch eine Gruppe von Ratern auf der Grundlage von Fotografien beurt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
2
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(25 citation statements)
references
References 42 publications
1
21
2
1
Order By: Relevance
“…In Finnish national elections, Berggren, Jordahl and Poutvaara (2006) found that a one standard deviation increase in beauty implies an increase of 2.5–2.8 percentage points in the voteshare of female candidates and 1.5–2.1 percentage points for male candidates. In German national elections, Klein and Rosar (2005) found that a one standard deviation increase in beauty was associated with a 1.5 percentage point increase in voteshare for female candidates and 0.6 percentage points for male candidates. Yet while the magnitude of the effects is quite similar across the three countries, the difference in Australia is that the marginal effect of beauty is smaller for male candidates than for female candidates.…”
Section: Resultsmentioning
confidence: 99%
“…In Finnish national elections, Berggren, Jordahl and Poutvaara (2006) found that a one standard deviation increase in beauty implies an increase of 2.5–2.8 percentage points in the voteshare of female candidates and 1.5–2.1 percentage points for male candidates. In German national elections, Klein and Rosar (2005) found that a one standard deviation increase in beauty was associated with a 1.5 percentage point increase in voteshare for female candidates and 0.6 percentage points for male candidates. Yet while the magnitude of the effects is quite similar across the three countries, the difference in Australia is that the marginal effect of beauty is smaller for male candidates than for female candidates.…”
Section: Resultsmentioning
confidence: 99%
“…This finding appears to be robust across countries, cultures, and contexts, including in elections. Attractive candidates have been shown to win more votes in elections to the national parliaments of Australia (King & Leigh, 2006), Finland (Berggren, Jordahl, & Poutvaara, 2006) and Germany (Klein & Rosar, 2005). In the US, candidates whose faces were judged to be more competent won more votes in actual elections (Todorov, Mandisodza, Goren, & Hall, 2005).…”
Section: A Simple Model Of Candidate Cuesmentioning
confidence: 99%
“…Some evidence exists on elections and beauty, with researchers finding a positive effect of beauty in elections to become an officer of the American Economic Association (Hamermesh 2006) or a member of a British community board (Banducci et al 2003). In national elections, more beautiful candidates have been found to do better in elections to the national parliaments of Finland (Berggren, Jordahl and Poutvaara 2006) and Germany (Klein and Rosar 2005). In the US, candidates whose faces were judged to be more competent won more votes in actual elections (Todorov et al 2005).…”
Section: Introductionmentioning
confidence: 99%